Ingeniería de reservorios geotérmicos - Hiriart L., Gerardo; Rivera, Jesús; Córdoba, Jesús; Herrera, Ismael; Aragón, Alfonso (My University, 1974)
Geothermal energy has received much attention in recent years as one of the sources that can help relieve help the energy crisis in the next decade. There is considerable literature on the possible methods of geothermal energy extraction, and practical usage of geothermal energy is growing worlvide. The goal of any geothermal production system is to extract heat form the earth, and to extract is at high enough temperature and rate that it can be used commercially to generate power or process heat.
Keywords: termodinámica; reservorios; flujo; presión; modelos